#27 ONE STOP BAKING CENTER - Vania Valentina; Tri Noviyanto P. Utomo; M. Y Susan (Universitas Ciputra Surabaya, 2016)
The background of this project is from the owner’s business, which is engaged to baking activities. As we know, baking is a method of cooking food that uses prolonged dry heat, normally in an oven. The most common item to bake is bread or cake. Baking techniques are not same as another technique. It needs an accurate of ingredients mix, texture, heat, and soon for obtaining the best result. In the other hand, aesthetic visual quality is important too. It is purposely to ensure the customer regarding the food, and also giving some economic values for the products. There are some services in #27 One Stop Baking Center; baking course activity, cake decoration course, kitchen rental, and bake ware, including ingredients retail store. This business planned to be opened in Mataram. Based on the survey that has been done, there are a lot of Mataram’s societies that are interested in baking activities. They want to learn something new or just use their spare time for a useful activity. The influence of architecture and interior design in this business is for the purpose of giving a new innovative way in creating a new image of a baking store as well as for giving new inspirations and information. Architectural and interior design are important to support the people in doing indoor activities, therefore it could increase the life quality for the users.